\(\frac{1}{2}\)- (x+\(\frac{3}{4}\))=\...">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

1 tháng 1 2017

1, \(\frac{1}{2}\)- (x + \(\frac{3}{4}\))= \(\frac{5}{6}\)

               (x+\(\frac{3}{4}\)) = \(\frac{5}{6}\)+  \(\frac{1}{2}\)

               ( x+ \(\frac{3}{4}\))=\(\frac{4}{3}\)

                 x             = \(\frac{4}{3}\)\(\frac{3}{4}\)

                x              =\(\frac{7}{12}\)

kết quả : k mk nha

2: =>2x-1/4=5/6-1/2x

=>5/2x=5/6+1/4=13/12

=>x=13/30

3: =>3x-5/6=2/3-1/2x

=>3,5x=2/3+5/6=4/6+5/6=9/6=3,2

hay x=32/35

2 tháng 8 2016

a)\(\frac{1}{4}-\frac{1}{3}x=\frac{2}{5}-\frac{3}{2}x\)

\(\Leftrightarrow\)\(\frac{15-20x}{60}=\frac{24-90x}{60}\)

\(\Leftrightarrow15-20x=24-90x\)

\(\Leftrightarrow-20x+90x=24-15\)

\(\Leftrightarrow70x=9\)

\(\Leftrightarrow x=\frac{9}{70}\)

 

c) (1/2-1/6)*3^x+4-4*3^x=3^16-4*3^13

=1/3*3^x*3^4-4*3^x=3^13*3^3-4*3^13

=27*3^x-4*3^x=3^13*(27-4)

=3^x*(27-4)=3^13*(27-4)

=>x=13

23 tháng 7 2017

/x/3+1/=2/3

(=)x/3+1=2/3 hoặc -2/3

Trường hợp 1: x/3+1=2/3

                      =) x/3= 2/3-1 

                      =) x/3=-1/3

                      =)X=-1

a: =>x-8/5=1/20-1/10=-1/20

=>x=-0,05+1,6=1,55

b: =>x-3/2=4/3 hoặc x-3/2=-4/3

=>x=17/6 hoặc x=1/6

c: =>\(\left|x-\dfrac{1}{3}\right|=\dfrac{5}{2}-\dfrac{1}{4}+\dfrac{2}{3}=\dfrac{35}{12}\)

=>x-1/3=35/12 hoặc x-1/3=-35/12

=>x=39/12=13/4 hoặc x=-31/12

d: =>|x-5/8|=3/4

=>x-5/8=3/4 hoặc x-5/8=-3/4

=>x=11/8 hoặc x=-1/8